P PENINGKATAN LITERASI KEUANGAN DAN EDUKASI PENGELOLAAN KEUANGAN BAGI PELAKU UMKM DI KELURAHAN OLAK KEMANG - Netty Herawaty; Sri Rahayu; Ratih Kusumastuti; Rahayu Rahayu; Widya Sari Wendry (Universitas Sumatera Barat, 2025)
The main objective of this community service is to improve the understanding and practical skills of MSME partners in financial literacy and management as a fundamental strategy to increase their business competitiveness. The main problems faced by MSME partners include (1) a lack of understanding of the importance of financial literacy; (2) a lack of structured transaction recording practices in accordance with accounting standards; and (3) the lack of a clear separation between personal and business finances. This results in weak control over cash flow and difficulties in determining working capital and business profitability. The method used in this activity is an educational approach through interactive lectures and technical assistance. The activity is carried out in several stages, including a preliminary survey, program socialization, training implementation (focusing on the importance of financial literacy, fund separation, and income-expenditure recording practices), activity evaluation, and program sustainability planning. It is hoped that through this community service, MSME actors in Olak Kemang Village will not only understand the theory but also be able to implement good financial management, so that simple financial reports can be presented, business capital can be managed well, and ultimately be able to encourage sustainable growth and MSME competitiveness.